(untitled) (Practicum Psychologia, 2026)
The study investigated the relationship between perceived knowledge of cardiovascular disease risk and health seeking behaviour in Omambala Area of Anambra State. A total number of 131 patients drawn from Omambala Area (Umueri General Hospital and Immaculate Heart Multispecialty Hospital, Aguleri) Anambra East Local Government Area, were used in the study. The study utilized non-probability (purposive sampling technique) in selecting the hospitals and participants. The participants’ age ranged from 45 to 79 years with mean age of 64.08 and standard deviation of 9.66. Gender data revealed that 33(25.2%) were males and 98(74.8%) were females. Awareness of Cardiovascular Disease Risk Questionnaire and Health Seeking Behavior scale were employed for the study. The study adopted correlational design and Multiple Linear Regression statistics. Results showed that perceived knowledge of cardiovascular disease risk dimensions such as perceived risk of heart attack/stroke at (F11, 119) β= .46, t = 7.07, and perceived benefits and intention to change at (F11, 119) β= .51, t = 8.52 had positive prediction on health seeking behaviour at p<.05. Whereas perceived eating intentions at (F11, 119) β= -.35, t = -2.99, had negative prediction on health seeking behaviour at p<.05. These findings suggest that programs that focus on increasing awareness of perceived risks for cardiovascular disease risk should be organized with emphasizing on the importance of lifestyle changes and messages that foster health seeking behaviour.